Electrode material and preparation method thereof, negative plate, battery, battery pack and electric equipment

By preparing electrode materials with a cavity shell structure, the problems of difficult lithium ion insertion and extraction, poor conductivity and easy structural damage of metal oxide negative electrode materials in lithium-ion batteries are solved, and the high rate performance and long cycle stability of the battery are achieved.

CN120727769APending Publication Date: 2025-09-30BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510652560.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-20
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

Metal oxides as negative electrode materials in lithium-ion batteries have problems such as difficulty in lithium ion insertion and extraction, poor conductivity, and easy structural damage, which affect the battery's rate capability and cycle stability.

Method used

An electrode material with a cavity shell structure is used. The shell is composed of a carbon matrix and metal oxide nanoparticles, which are combined by chemical bonds to form a capsule or capsule-like structure. It is prepared by hydrothermal reaction and sintering treatment of MOFs material and etchant.

Benefits of technology

It significantly improves the battery's rate capability and cycle stability, enhances the conductivity and bonding strength of metal oxide nanoparticles, alleviates volume changes during charging and discharging, and improves charge transfer kinetics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120727769A_ABST
    Figure CN120727769A_ABST
Patent Text Reader

Abstract

The invention provides an electrode material and a preparation method thereof, a negative plate, a battery, a battery pack and electric equipment, the electrode material comprises a shell, the shell comprises a shell wall and a cavity enclosed by the shell wall, and the shell wall comprises a carbon matrix and metal oxide nanoparticles arranged on at least part of the surface of the carbon matrix. The electrode material disclosed by the invention has a special shell structure, so that the rate capability and the cycling stability of the metal oxide electrode material can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to an electrode material and a preparation method thereof, a negative electrode sheet, a battery, a battery pack and an electrical device. Background Art

[0002] With the increasing popularity of electronic devices and the demand for portable power sources, lithium-ion batteries have become an indispensable energy source in modern society. From smartphones to electric vehicles, lithium-ion batteries are used in nearly every field. To improve battery performance, especially high energy density and long-term stability, the development of high-performance anode materials has become one of the keys to improving overall battery efficiency.

[0003] Metal oxides as negative electrode materials generally have a high theoretical specific capacity, which means they have the potential to provide higher energy density. However, when metal oxides are used as electrode materials for lithium-ion batteries, the following problems are generally encountered: 1) Due to the strong electrostatic force between metal oxides and lithium ions, this hinders the rapid insertion and extraction of lithium ions, affecting the battery's rate performance; 2) The metal oxides themselves have poor electronic conductivity, which further limits the battery's rate performance; 3) During the charge and discharge process, especially in high temperature environments, the crystal structure of the metal oxide is easily destroyed, resulting in material pulverization and destruction of the electrode structure, thereby affecting the battery's cycle stability. Summary of the Invention

[0004] The present invention provides an electrode material. Due to its special shell structure, the electrode material can significantly improve the rate capability and cycle stability of metal oxide electrode materials.

[0005] The present invention also provides a method for preparing the above electrode material, which can prepare the electrode material.

[0006] The present invention also provides a negative electrode sheet. Since the negative electrode sheet includes the above-mentioned electrode material, the negative electrode sheet has the advantages of good cycle stability and high charge and discharge efficiency.

[0007] The present invention also provides a battery. Since the battery includes the negative electrode sheet, the battery has good cycle performance and excellent rate capability.

[0008] The present invention also provides a battery pack. Since the battery pack includes at least two of the above batteries, the battery pack has good cycle performance and excellent rate capability.

[0009] The present invention also provides an electrical device, which includes the above-mentioned battery or battery pack and has good long service life and high charging and discharging efficiency.

[0010] In a first aspect, the present invention provides an electrode material, comprising a shell, the shell comprising a shell wall and the cavity surrounded by the shell wall, the shell wall comprising a carbon matrix and metal oxide nanoparticles arranged on at least a portion of the surface of the carbon matrix.

[0011] Optionally, the carbon matrix includes a plurality of carbon particles, and the plurality of carbon particles are interconnected to form the shell.

[0012] Optionally, at least part of the carbon matrix and at least part of the metal oxide nanoparticles are bonded via chemical bonds.

[0013] Optionally, the chemical bond comprises a carbon-oxygen-metal bond.

[0014] Optionally, the electrode material is a single crystal structure.

[0015] Optionally, the thickness of the shell wall is 5-20 nm, and the particle size of the shell is 200-500 nm.

[0016] Optionally, the shell is a capsule or a capsule-like structure.

[0017] Optionally, the length of the shell is 450-550 nm, and the width of the shell is 150-250 nm.

[0018] Optionally, the shell includes a first pore channel with a pore diameter of 8-9 nm, and the porosity of the first pore channel is 0.4%-0.6%.

[0019] Optionally, the shell further includes a second pore channel with a pore diameter of 2-3 nm, and the porosity of the first pore channel is 0.3%-0.4%.

[0020] Optionally, the metal oxide nanoparticles include at least one of vanadium oxide, iron oxide, and copper oxide.

[0021] And / or, the carbon matrix is ​​a heteroatom-doped carbon material.

[0022] Optionally, the heteroatom includes at least one of a nitrogen atom, a sulfur atom, and a phosphorus atom.

[0023] Optionally, the particle size of the metal oxide nanoparticles is 5-20 nm;

[0024] And / or, the mass ratio of the metal oxide nanoparticles to the carbon matrix is ​​6-8:2-4.

[0025] In a second aspect, the present invention provides a method for preparing an electrode material as described in the first aspect, comprising the following steps:

[0026] A mixed system including MOFs material, an etchant and a solvent is subjected to a hydrothermal reaction to obtain a MOFs material having a cavity;

[0027] The MOFs material with a cavity is sintered to obtain the electrode material.

[0028] Optionally, the atmosphere of the sintering treatment includes at least one of oxygen, argon, and nitrogen;

[0029] And / or, the hydrothermal reaction temperature is 180-200° C. and the time is 10-15 h;

[0030] And / or, the sintering treatment temperature is 600-800° C. and the time is 1-3 hours.

[0031] Optionally, the etchant contains a functional group capable of coordinating with the MOFs material;

[0032] And / or, the MOFs material includes at least one of NH2-MIL88B, OH-MIL88B, and MIL88B.

[0033] Optionally, the etchant includes at least one of 2,4,6-tris-(4-pyridyl)pyridine and 2,4,6-tris-(4-pyridyl)triazine.

[0034] Optionally, the mass ratio of the MOFs material to the etchant is 1-2:1-2.

[0035] In a third aspect, the present invention provides a negative electrode sheet comprising the electrode material as described in the first aspect.

[0036] In a fourth aspect, the present invention provides a battery comprising the negative electrode sheet as described in the third aspect.

[0037] In a fifth aspect, the present invention provides a battery pack comprising at least two batteries as described in the fourth aspect.

[0038] In a sixth aspect, the present invention provides an electrical device comprising the battery as described in the fourth aspect or the battery pack as described in the fifth aspect.

[0039] The electrode material provided by the present invention can significantly improve the rate capability and cycle stability of the battery. Specifically, the introduction of the carbon matrix in the electrode material can improve the conductivity of the metal oxide nanoparticles, and because the carbon matrix and the metal oxide nanoparticles form a shell with a cavity, the bonding strength between the two can be significantly increased compared to ordinary physical mixing. Secondly, the electrode material with a cavity shell can shorten the diffusion distance of metal ions and improve the charge transfer kinetics, thereby improving the rate capability of the electrode material; and the high surface area of ​​the shell and the large accommodating space of the cavity can provide abundant active sites for metal ion storage, which can alleviate the volume change caused by the insertion / extraction of lithium ions during the charge and discharge cycle, thereby helping to improve the structural stability of the electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0041] Figure 1 This is the X-ray powder diffraction spectrum of the capsule MOFs of Example 5 of the present invention;

[0042] Figure 2 This is a scanning electron microscope image of the capsule MOFs of Example 5 of the present invention;

[0043] Figure 3 This is a graph showing the nitrogen adsorption-desorption isotherm test results of the capsule MOFs of Example 5 of the present invention;

[0044] Figure 4 A synthetic route for an electrode material according to a specific embodiment of the present invention;

[0045] Figure 5 is the X-ray powder diffraction spectrum of the electrode material of Example 5 of the present invention;

[0046] Figure 6 This is a transmission electron microscope image of the electrode material of Example 5 of the present invention. DETAILED DESCRIPTION

[0047] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific embodiments listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts are within the scope of protection of the present invention.

[0048] In this application, the terms "first" and "second" are used solely for descriptive purposes to distinguish objects, such as substances, from one another and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. For example, without departing from the scope of the embodiments of this application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" or "second" may explicitly or implicitly include one or more of such features.

[0049] Throughout this application, references to "one embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in connection with that embodiment, embodiment, or example is included in at least one embodiment of the present invention. Therefore, appearances of the phrases "one embodiment," "an embodiment," "an example," or "an example" in various places throughout this specification are not necessarily all referring to the same embodiment or example. Furthermore, the particular features, structures, or characteristics may be combined in any suitable combinations and / or subcombinations in one or more embodiments or examples.

[0050] In order to improve the conductivity and stability of metal oxides, the commonly used improvement methods mainly include the following two: (1) doping metal oxides with highly conductive carbon materials such as graphene and carbon nanotubes; (2) designing and synthesizing nano-sized metal oxides with large specific surface areas and special morphologies. Among them, doping carbon materials with metal oxides often has a weak bonding force between the two, so there is still a stability problem. Designing and synthesizing metal oxides with large specific surface areas, due to the easy agglomeration of nanoparticles, leads to a reduction in specific surface area, which affects the contact area between them and lithium ions.

[0051] Micro-nanocapsules, due to their high surface area, modifiable shell structure, and large accommodation space, facilitate sufficient contact between electrode materials and electrolytes, accelerating electrolyte penetration. Furthermore, the hollow capsules of micro-nanocapsules are expected to alleviate the volume changes caused by the insertion / extraction of lithium ions during the charge-discharge cycle. Therefore, designing the electrode materials into capsules or capsule-like hollow shell structures can solve the above problems. Specifically, the present invention provides the following technical solutions:

[0052] In a first aspect, the present invention provides an electrode material, comprising a shell having a cavity, wherein the shell comprises a shell wall and the cavity surrounded by the shell wall, wherein the shell wall comprises a carbon matrix and metal oxide nanoparticles arranged on at least a portion of the surface of the carbon matrix.

[0053] Among them, the electrode material provided by the present invention can significantly improve the rate capability and cycle stability of the battery. The main reasons include: in the electrode material, the introduction of the carbon matrix can improve the conductivity of the metal oxide nanoparticles, and because the carbon matrix and the metal oxide nanoparticles constitute a shell with a cavity, the bonding strength between the two can be significantly increased compared to ordinary physical mixing. Secondly, the electrode material with a cavity shell also has the following functions: ① The shell structure can shorten the diffusion distance of metal ions and improve the charge transfer kinetics, thereby improving the rate capability of the electrode material; ② The high surface area of ​​the shell and the large accommodating space of the cavity can provide abundant active sites for metal ion storage, which can alleviate the volume change caused by the insertion / extraction of lithium ions during the charge and discharge cycle, thereby helping to improve the structural stability of the electrode material.

[0054] It should be noted that at least part of the surface of the above-mentioned carbon matrix can be the outer surface or the inner surface; the metal oxide nanoparticles can be any metal oxide that allows the transmission of metal ions such as lithium, for example, including but not limited to: iron oxide, copper oxide, nickel oxide, etc.

[0055] In addition, the metal oxide nanoparticles are nano-sized, and the present invention does not particularly limit the specific particle size. In some embodiments, the particle size of the metal oxide nanoparticles is 1-10 nm.

[0056] In a specific embodiment, the carbon matrix includes a plurality of carbon particles, and the plurality of carbon particles are interconnected to form the shell.

[0057] Among them, the shell in this embodiment is formed by interconnected carbon particles, which can be understood as a carbon shell with a cavity, and the metal oxide nanoparticles are distributed on the inner surface, outer surface or between the carbon particles of the carbon shell, etc., thereby further improving the conductivity of the shell and further alleviating the volume change caused by the insertion / extraction of lithium ions during the charge and discharge cycle.

[0058] In one embodiment, at least a portion of the carbon matrix and at least a portion of the metal oxide nanoparticles are bonded via chemical bonds.

[0059] Among them, the above-mentioned embodiment can further enhance the bonding force between the carbon matrix and the metal oxide nanoparticles, which is more conducive to inhibiting the agglomeration of the metal oxide nanoparticles and improving the structural integrity of the electrode material during long-term use.

[0060] In one embodiment, the chemical bond comprises a carbon-oxygen-metal bond.

[0061] The chemical bond described above can further ensure the binding force between the carbon matrix and the metal oxide nanoparticles.

[0062] In one embodiment, the electrode material is a single crystal structure.

[0063] Among them, materials with a single crystal structure are composed of a continuous lattice structure, with highly ordered atomic arrangement throughout the material and no grain boundaries. Materials with a polycrystalline structure, on the other hand, are composed of many small grains, each of which is a single crystal, but with grain boundaries between them. Electrode materials made of single crystal materials have higher conductivity and mechanical strength, and they exhibit excellent performance in electronic devices, such as higher electron mobility. Electrode materials with a polycrystalline structure lead to scattering of electrons and ions, reducing conductivity. In addition, grain boundaries may also become stress concentration points, affecting the mechanical properties of the material.

[0064] In a specific embodiment, the thickness of the shell wall is 5-20 nm, and the particle size of the shell is 200-500 nm.

[0065] In the embodiment described above, the shell wall is thinner and the particle size is moderate, which can further ensure the high mechanical stability of the electrode material, further shorten the diffusion distance of metal ions, improve the charge transfer kinetics, and thus improve the rate capability of the electrode material.

[0066] Exemplarily, the thickness of the shell wall is any value among 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, etc., or a range consisting of any two of them; the particle size of the shell refers to the maximum size of the shell, which can be any value among 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, etc., or a range consisting of any two of them.

[0067] In one embodiment, the shell is a capsule or a capsule-like structure.

[0068] The shell of the capsule or capsule-like structure has a high surface area and large accommodation space, which can provide more abundant active sites for metal ion storage, further alleviate the volume changes caused by lithium ion insertion / extraction during the charge and discharge cycle, thereby significantly improving the structural stability of the electrode material.

[0069] In a specific embodiment, the length of the shell is 450-550 nm, and the width of the shell is 150-250 nm.

[0070] The length of the shell refers to the size of the shell in the direction of the long axis, and the width of the shell refers to the size of the shell in the direction of the short axis, which can be specifically obtained through TEM characterization and measurement.

[0071] In a specific embodiment, the shell includes a first pore channel with a pore diameter of 8-9 nm, and the porosity of the first pore channel is 0.4%-0.6%.

[0072] Among them, the shell as described above has sufficient mesoporous channels, which can further increase the fast channels of metal ions and improve the charge transfer kinetics. At the same time, the multi-mesoporous shell can further alleviate the volume changes caused by the insertion / extraction of metal ions during the charge and discharge cycle, thereby helping to further improve the cycle stability of the battery.

[0073] The porosity of the first pore channel or the second pore channel refers to the volume ratio of the pore channel to the total material.

[0074] In some embodiments, the pore size and porosity of the first channel can be tested by a gas adsorption method (BET method).

[0075] In a specific embodiment, the shell further includes a second pore channel with a pore diameter of 2-3 nm, and the porosity of the first pore channel is 0.3%-0.4%.

[0076] When the shell further includes second pores in the above ratio, it helps to increase the lithium storage capacity of the electrode material because the second pores can provide more lithium ion storage sites.

[0077] In a specific embodiment, the metal oxide nanoparticles include at least one of vanadium oxide, iron oxide, and copper oxide.

[0078] Among them, vanadium can show a variety of valence states, such as V 3+ 、V 4+ and V 5+ Its oxides are more conducive to the transmission of metal ions due to their pores or layered structures; iron is one of the most abundant elements in the earth's crust, so iron oxide has the advantages of low cost and abundant resources, which makes it advantageous in green battery technology; copper oxide has good conductivity, can improve the electron transmission efficiency of electrode materials, and is suitable for use in high-energy-density batteries.

[0079] In one embodiment, the carbon matrix is ​​a heteroatom-doped carbon material.

[0080] Doping with heteroatoms can change the electronic structure of the carbon matrix and increase its conductivity, which helps to improve the efficiency of electron transmission in the electrode material and thus enhance the rate performance of the battery.

[0081] In one embodiment, the heteroatom includes at least one of a nitrogen atom, a sulfur atom, and a phosphorus atom.

[0082] The heteroatoms mentioned above can improve the efficiency of electron transfer in the electrode material while also enhancing the interfacial stability between the carbon material and the electrolyte, reducing the occurrence of side reactions, which helps to improve the cycle stability and life of the battery.

[0083] In one embodiment, the metal oxide nanoparticles have a particle size of 5-20 nm.

[0084] Among them, metal oxide nanoparticles with the above particle size can further improve the conductivity of the shell.

[0085] Illustratively, the particle size of the metal oxide nanoparticles is any value among 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, etc., or a range consisting of any two of them.

[0086] In a specific embodiment, the mass ratio of the metal oxide nanoparticles to the carbon matrix is ​​6-8:2-4.

[0087] The carbon matrix and metal oxide nanoparticles in the above mass ratio can not only further ensure the conductivity of the shell, but also further alleviate the volume change caused by the insertion / extraction of lithium ions during the charge and discharge cycle.

[0088] Metal-organic frameworks (MOFs) are microporous coordination polymers assembled from metal ions and organic ligands through coordination bonds. They show great potential for synthesizing encapsulated crystals. Existing processes typically use inactive solids as internal templates to prefabricate core-shell intermediates. However, this method is complex and difficult to remove the template. In recent years, researchers have developed self-templating methods to prepare hollow MOF crystals without coring, but most preparation methods result in polycrystalline hollow structures filled with small MOF crystals.

[0089] The present invention discovered that the kinetic control of MOFs dissolution-regrowth has a significant impact on the crystal morphology. When the structures of the mother crystal and the shell crystal are closely matched, the shell crystal will grow evenly on the outer surface of the mother crystal, while the core of the mother crystal simultaneously dissolves and diffuses outward. This mass transfer process from the core to the surface leads to the formation of a single crystal envelope structure, leaving a large number of pores on the wall. To this end, the second aspect of the present invention provides a method for preparing the electrode material as described in the first aspect, comprising the following steps:

[0090] A mixed system including MOFs material, an etchant and a solvent is subjected to a hydrothermal reaction to obtain a MOFs material having a cavity;

[0091] The MOFs material with a cavity is sintered to obtain the electrode material.

[0092] The preparation method described above is to heat-decompose MOFs materials and etchants to transform solid MOFs nanocrystals into hollow shells, which are then sintered to form a carbon shell uniformly distributed with metal oxide nanoparticles (taking V-NH2-MIL88B as an example, the synthesis route of electrode materials can be found in Figure 4 The above method can not only achieve uniform compounding between metal oxide nanoparticles and carbon matrix, but also avoid agglomeration of metal oxide nanoparticles, thus further ensuring the stability of electrode materials.

[0093] The composition of metal oxide nanoparticles and carbon-based materials in electrode materials can be achieved by controlling the composition of MOFs materials.

[0094] Secondly, the type of the above-mentioned atmosphere can be adjusted according to the metal valence state of the desired metal oxide.

[0095] In a specific embodiment, the atmosphere of the sintering process includes at least one of oxygen, argon, and nitrogen.

[0096] In one embodiment, the hydrothermal reaction temperature is 180-200° C., and the time is 10-15 hours.

[0097] The hydrothermal reaction described above can ensure that the solid MOFs nanocrystals can be transformed into hollow shells.

[0098] In a specific embodiment, the sintering treatment is performed at a temperature of 600-800° C. and for a time of 1-3 hours.

[0099] The sintering process described above can form a carbon matrix and further regulate the pore size and distribution of the electrode material.

[0100] In one embodiment, the etchant contains a functional group capable of coordinating with the MOFs material.

[0101] The above-mentioned etchant can coordinate with the metal center of the MOFs material, thereby kinetically controlling the dissolution-regrowth of MOFs to achieve an etching effect on the center of the MOFs material.

[0102] In a specific embodiment, the MOFs material includes at least one of NH2-MIL88B, OH-MIL88B, and MIL88B.

[0103] The MOFs material described above can obtain a shell specifically including metal oxide nanoparticles and carbon-based materials, thereby further ensuring the stability and ion transport properties of the electrode material.

[0104] In a specific embodiment, the organic ligand of the MOFs material includes at least one of terephthalic acid, hydroxyterephthalic acid, and aminoterephthalic acid.

[0105] In a specific embodiment, the etchant includes at least one of 2,4,6-tris-(4-pyridyl)pyridine and 2,4,6-tris-(4-pyridyl)triazine.

[0106] In a specific embodiment, the mass ratio of the MOFs material to the etchant is 1-2:1-2.

[0107] In a third aspect, the present invention provides a negative electrode sheet comprising the electrode material as described in the first aspect.

[0108] In some embodiments, the negative electrode sheet further includes a conductive agent, a binder and a dispersant, wherein the conductive agent can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, metal powder, and graphene; the binder can be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate; the dispersant can be selected from at least one of sodium carboxymethyl cellulose, triethylhexyl phosphoric acid, and sodium lauryl sulfate.

[0109] In a fourth aspect, the present invention provides a battery comprising the negative electrode sheet as described in the third aspect.

[0110] In some embodiments, in addition to the negative electrode provided by the present invention, a positive electrode, an electrolyte, and a separator are also included. During the battery's charge and discharge process, active metal ions are intercalated and released between the positive and negative electrodes, and the electrolyte acts as an ion conductor between the positive and negative electrodes. The separator is positioned between the positive and negative electrodes, primarily preventing short circuits between the positive and negative electrodes while allowing ions to pass through.

[0111] This application does not limit the type of separator; any separator material used in existing batteries can be used. Examples include, but are not limited to, single-layer PP (polypropylene) film, single-layer PE (polyethylene) film, double-layer PP / PE film, double-layer PP / PP film, and triple-layer PP / PE / PP film.

[0112] The present application does not limit the positive electrode active material in the positive electrode sheet, which can be a positive electrode active material commonly used in existing batteries. For example, the positive electrode active material includes but is not limited to at least one composite oxide of lithium and a metal selected from the group consisting of cobalt, manganese, nickel, and combinations thereof.

[0113] The battery of the present invention can be manufactured according to conventional methods in the field. For example, the positive electrode sheet, the separator, and the negative electrode sheet can be stacked in sequence, and then assembled into a battery cell through a winding process or a stacking process. Then, after packaging and baking, the electrolyte is injected, and the battery is manufactured after processes such as hot pressing.

[0114] In a fifth aspect, the present invention provides a battery pack comprising at least two batteries as described in the fourth aspect.

[0115] Generally, a battery pack includes at least two of the above-mentioned batteries, which are connected as single cells to form a battery pack. The batteries can be electrically connected by conventional methods in the art, such as series connection, parallel connection, or a combination of these connection methods.

[0116] In a sixth aspect, the present invention provides an electrical device comprising the battery as described in the fourth aspect or the battery pack as described in the fifth aspect.

[0117] The electrical equipment in the embodiments of the present invention can be conventional electrical equipment in this field, such as power equipment (such as electric vehicles, electric cars), electronic equipment (such as mobile phones, tablets, laptops, digital cameras, etc.), wearable devices (such as watches, bracelets, VR glasses, etc.), energy storage power stations, etc., without special restrictions.

[0118] The technical solutions of the present invention are further illustrated below with reference to specific examples. All parts, percentages, and ratios described in the following examples are based on weight. All reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment. The instruments used in the examples are commercially available.

[0119] Synthesis of V–NH2–MIL88B: A mixture of vanadium(III) trichloride (VCl3, 1.57 g, 10.0 mmol) and 2-aminoterephthalic acid (1.81 g, 10.0 mmol) was dissolved in anhydrous ethanol (50 mL) and sonicated for 30 minutes. Subsequently, 10 mL of 2 M aqueous hydrochloric acid was added dropwise to the solution with stirring. The resulting solution was sonicated for 15 minutes and then transferred to a 100 mL autoclave and heated at 120°C for 48 hours. The green solid was then collected by centrifugation and washed several times with anhydrous ethanol until the supernatant was colorless. The resulting solid was dried in a vacuum oven at 120°C for 16 hours to obtain the green product, V–NH2–MIL88B.

[0120] The synthesis of Fe–NH2–MIL88B and Ni–NH2–MIL88B differs from the above process only in that VCl3 is replaced by FeCl3 and NiCl2.

[0121] Example 1

[0122] This example provides an electrode material, the preparation method of which includes the following steps:

[0123] 1) A mixture of V–NH2–MIL88B (200 mg) and 2,4,6-tris-(4-pyridyl)pyridine (tpy, 100 mg) was transferred to a 25 mL autoclave, and 10 mL of N,N-dimethylformamide (DMF) was added. The mixture was heated at 190°C for 12 hours. After cooling, the solid was centrifuged and washed with DMF and methanol until the washings were colorless, yielding a light green solid powder. This was dried in vacuo at 100°C for 4 hours to obtain the encapsulated MOFs (200 mg, ~67% yield).

[0124] 2) 500 mg of MOF capsules were calcined at 600 °C in an Ar atmosphere for 1 hour to obtain the electrode material.

[0125] Examples 2-9

[0126] The difference from Example 1 is that the capsule MOFs in step 2) are calcined at different temperatures for different times, as shown in Table 1.

[0127] Example 10

[0128] The difference from Example 1 is that the metal center of V–NH2–MIL88B in step 1) is replaced with Fe, as shown in Table 1.

[0129] Example 11

[0130] The difference from Example 1 is that the V–NH2–MIL88B metal center in step 1) is replaced with Ni, as shown in Table 1.

[0131] Comparative Example 1

[0132] In this example, graphite is directly used as the electrode material, and its particle size is 10 μm.

[0133] Comparative Example 2

[0134] The difference from Example 1 is that V–NH2–MIL88B is directly calcined in an Ar atmosphere at 700°C for 2 hours to obtain an electrode material.

[0135] Test Example 1

[0136] The above electrode materials are formed into a negative electrode sheet, comprising the following steps:

[0137] The electrode material, conductive agent carbon black, binder SBR, and thickener CMC were mixed in a mass ratio of 95.5:1:1.5:2, and deionized water was added to stir into a uniform slurry; the negative electrode slurry was evenly coated on the negative electrode current collector copper foil, dried in an oven, and then roller-pressed to obtain a series of negative electrode sheets.

[0138] Test Example 2

[0139] Assembling the negative electrode sheet of Experimental Example 1 into a battery includes the following steps:

[0140] Positive electrode: Prepare a lithium foil counter electrode with a diameter of 16 mm and a smooth and bright surface.

[0141] Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are mixed in a volume ratio of 1:1:1 and an appropriate amount of vinylene carbonate (VC) is added to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L.

[0142] Preparation of isolation membrane: A polyethylene film coated with ceramic glue on both sides was selected as the isolation membrane.

[0143] Preparation of lithium-ion batteries: stack the above-mentioned negative electrode sheets, separators, and lithium sheets in order, so that the separator is between the negative and lithium sheets to isolate the two electrodes. Then, the electrode core is obtained by stacking the sheets, and the electrode core is placed in the outer packaging shell. The electrolyte is injected and the lithium-ion battery is obtained after the processes of packaging, standing, formation, and capacity separation.

[0144] Test Example 1

[0145] The crystal structure, pore distribution and morphology characteristics of the intermediate product capsule MOFs and the final product electrode material of each embodiment and comparative example were tested, specifically including:

[0146] ① Powder X-ray diffraction (PXRD) spectrum was obtained using a Cu-Kα light source. The powder X-ray diffractometer was used to collect the data.

[0147] ②N2 adsorption / desorption isotherm test After the sample was activated under vacuum conditions at 100 °C for 12 hours, it was measured at 77 K using a Micromeritics ASAP 2020Plus HD88 automatic gas adsorption instrument.

[0148] ③ Field emission scanning electron microscopy (FESEM) and energy dispersive spectroscopy (EDS) were performed using a MERLIN Compact microscope at an accelerating voltage of 20 kV. Transmission electron microscopy (TEM) images were taken using a Talos F200X G2.

[0149] The above results are summarized in Table 1.

[0150] in, Figure 1 This is the X-ray powder diffraction spectrum of the capsule MOFs of Example 5. From the results, it can be seen that the capsule MOFs of Example 5 have clear crystal structure characteristics, and its diffraction peak position is highly consistent with the simulation spectrum, and no impurity phase peak is observed, indicating that a single crystal phase product is successfully obtained.

[0151] Figure 2 This is an electron scanning microscope image of the capsule MOFs of Example 5. From the results, it can be seen that the electrode material of Example 5 has capsule structural characteristics. The length and width of the capsule are distributed in the range of 200-500nm, with a specific length of about 500nm (long axis direction), a width of about 200nm (short axis direction), and a wall thickness of about 10nm.

[0152] Figure 3 The nitrogen adsorption-desorption isotherm test results of the encapsulated MOFs of Example 5 show that the encapsulated MOFs of Example 5 exhibit significant type IV isotherm characteristics within the relative pressure range of P / P0 = 0.4-0.9, accompanied by an H3-type hysteresis loop, which is closely related to its mesoporous-dominated pore structure. In contrast, V-NH2-MIL88B exhibits a typical type II isotherm, which is directly related to its dense three-dimensional network structure, resulting in a significant molecular sieving effect and diffusion limitation.

[0153] Figure 5 This is the X-ray powder diffraction spectrum of the electrode material of Example 5. The diffraction peak position is highly consistent with the simulated spectrum, and no impurity phase peak is observed.

[0154] Figure 6 This is a transmission electron microscope image of the electrode material of Example 5. The result shows that its electrode material structure is composed of a thin-walled hollow cavity with an internal cavity diameter of about 200-500nm, forming a significantly high specific surface area and internal load space. The nanoparticles are evenly dispersed. The reason may be that V2O3 and C-N form a strong interaction through C-O-V chemical bonding, which inhibits the agglomeration of nanoparticles.

[0155] Table 1:

[0156]

[0157] Test Example 2

[0158] The examples were subjected to cycle and rate tests respectively.

[0159] The batteries prepared in the examples were formed and capacity-scaled at room temperature, and then activated by three cycles of low-current charge and discharge. After these preparations, the batteries were tested. Discharge capacity tests were performed at 0.1C / 1C, with the results shown in Table 2 below.

[0160] The battery was tested for 45°C cycle capacity retention rate. The test process and results are as follows:

[0161] Test procedure: Ambient temperature: 45℃, start the test after 5 hours of storage; perform 45℃ cycle test according to the following procedure

[0162] ①Charging: 1C constant current charging to 3.0V, set aside for 10 minutes;

[0163] ②Discharge: 1C constant current to 0.01V, leave for 10 minutes;

[0164] ③ After 500 cycles, the capacity retention rate was calculated. The results are shown in Table 2 below.

[0165] Table 2:

[0166]

[0167] It can be seen from Table 2 that, compared with the comparative example, the electrode material of the embodiment can significantly increase the rate capability and high-temperature cycle stability of the battery.

[0168] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An electrode material, characterized in that The electrode material comprises a shell, the shell comprises a shell wall and the cavity surrounded by the shell wall, the shell wall comprises a carbon matrix and metal oxide nanoparticles arranged on at least a portion of the surface of the carbon matrix.

2. The electrode material according to claim 1, characterized in that The carbon matrix includes a plurality of carbon particles, and the plurality of carbon particles are interconnected to form the shell.

3. The electrode material according to claim 1 or 2, characterized in that At least part of the carbon matrix and at least part of the metal oxide nanoparticles are bonded via chemical bonds.

4. The electrode material according to claim 3, characterized in that The chemical bonds include carbon-oxygen-metal bonds.

5. The electrode material according to any one of claims 1 to 4, characterized in that The electrode material is a single crystal structure.

6. The electrode material according to any one of claims 1 to 5, characterized in that The thickness of the shell wall is 5-20 nm, and the particle size of the shell is 200-500 nm.

7. The electrode material according to claim 6, characterized in that The shell is a capsule or a capsule-like structure.

8. The electrode material according to claim 7, characterized in that The length of the shell is 450-550 nm, and the width of the shell is 150-250 nm.

9. The electrode material according to any one of claims 1 to 8, characterized in that The shell includes a first pore channel with a pore diameter of 8-9 nm, and the porosity of the first pore channel is 0.4%-0.6%.

10. The electrode material according to claim 9, characterized in that The shell further includes a second pore channel with a pore diameter of 2-3 nm, and a porosity of the second pore channel of 0.3%-0.4%.

11. The electrode material according to any one of claims 1 to 10, characterized in that The metal oxide nanoparticles include at least one of vanadium oxide, iron oxide, and copper oxide; And / or, the carbon matrix is ​​a heteroatom-doped carbon material.

12. The electrode material according to claim 11, characterized in that The heteroatom includes at least one of a nitrogen atom, a sulfur atom, and a phosphorus atom.

13. The electrode material according to any one of claims 2 to 12, characterized in that: The particle size of the metal oxide nanoparticles is 5-20 nm; And / or, the mass ratio of the metal oxide nanoparticles to the carbon matrix is ​​6-8:2-4.

14. A method for preparing an electrode material according to any one of claims 1 to 13, characterized in that: The following steps are involved: A mixed system including MOFs material, an etchant and a solvent is subjected to a hydrothermal reaction to obtain a MOFs material having a cavity; The MOFs material with a cavity is sintered to obtain the electrode material.

15. The preparation method according to claim 14, characterized in that The sintering atmosphere includes at least one of oxygen, argon and nitrogen; And / or, the hydrothermal reaction temperature is 180-200° C. and the time is 10-15 h; And / or, the sintering treatment temperature is 600-800° C. and the time is 1-3 hours.

16. The preparation method according to claim 14 or 15, characterized in that: The etchant contains a functional group capable of coordinating with the MOFs material; And / or, the MOFs material includes at least one of NH2-MIL88B, OH-MIL88B, and MIL88B.

17. The preparation method according to claim 16, characterized in that The etchant includes at least one of 2,4,6-tris-(4-pyridyl)pyridine and 2,4,6-tris-(4-pyridyl)triazine.

18. The preparation method according to claim 17, characterized in that: The mass ratio of the MOFs material to the etchant is 1-2:1-2.

19. A negative electrode sheet, characterized in that: The electrode material comprises the electrode material according to any one of claims 1 to 13.

20. A battery, characterized in that: Including the negative electrode sheet according to claim 19.

21. A battery pack, characterized in that: Comprising at least two batteries according to claim 20.

22. An electrical device comprising the battery according to claim 20 or the battery pack according to claim 21.